Detection and Structural Characterization of Nucleophiles Trapped Reactive Metabolites of Limonin Using Liquid Chromatography-Mass Spectrometry. (17th April 2018) - Deng, Yujie; Fu, Yudong; Xu, Shumin; Wang, Ping; Yang, Nailong; Li, Chengqian; Yu, Qing
Abstract : Limonin (LIM), a furan-containing limonoid, is one of the most abundant components of Dictamnus dasycarpus Turcz. Recent studies demonstrated that LIM has great potential for inhibiting the activity of drug-metabolizing enzymes. However, the mechanisms of LIM-induced enzyme inactivation processes remain unexplored. The main objective of this study was to identify the reactive metabolites of LIM using liquid chromatography-mass spectrometry. Three nucleophiles, glutathione (GSH), N -acetyl cysteine (NAC), and N -acetyl lysine (NAL), were used to trap the reactive metabolites of LIM in in vitro and in vivo models. Two different types of mass spectrometry, a hybrid quadrupole time-of-flight (Q-TOF) mass spectrometry and a LTQ velos Pro ion trap mass spectrometry, were employed to acquire structural information of nucleophile adducts of LIM. In total, six nucleophile adducts of LIM (M1–M6) with their isomers were identified; among them, M1 was a GSH and NAL conjugate of LIM, M2–M4 were glutathione adducts of LIM, M5 was a NAC and NAL conjugate of LIM, and M6 was a NAC adduct of LIM. Additionally, CYP3A4 was found to be the key enzyme responsible for the bioactivation of limonin. This metabolism study largely facilitates the understanding of mechanisms of limonin-induced enzyme inactivation processes.